Comparison of anticoagulants and risk factors for bleeding following endoscopic sphincterotomy among anticoagulant users: Results from a large multicenter retrospective study. Issue 1 (28th July 2019) - Muro, Shinichiro; Kato, Hironari; Ishida, Etsuji; Ueki, Toru; Fujii, Masakuni; Harada, Ryo; Seki, Hiroyuki; Hirao, Ken; Wato, Masaki; Akimoto, Yutaka; Takatani, Masahiro; Tsugeno, Hirofumi; et al.
Abstract: Background and Aim: Bleeding is an inevitable and often severe complication after endoscopic sphincterotomy (EST). We aimed to investigate the factors associated with post‐EST bleeding in patients treated with anticoagulants. Methods: The data of patients who underwent EST at 15 hospitals between July 2015 and June 2017 were extracted. We investigated the incidence of post‐EST bleeding and risk factors for bleeding in patients treated with anticoagulants. Results: One hundred forty‐nine patients undergoing EST who met the inclusion criteria were included in this study. The total‐EST bleeding (bleeding occurring during or after EST) rate did not differ between the heparin replacement (8.0%, 6/75) and continuation (16.6%, 2/12; P = 0.37) groups of warfarin users. The total‐EST‐bleeding rate in the heparin replacement group (12.9%, 4/31) was significantly higher than that in the continuation group (0%, 0/31; P = 0.016) in direct oral anticoagulant (DOAC) users. The rate of total‐EST bleeding with continuation of DOAC (0%, 0/31) was significantly lower with continuation of warfarin (16.6%, 2/12; P = 0.021). During‐EST bleeding (bleeding occurring during EST) ( P = 0.0083) and precut ( P = 0.033) were significant risk factors for post‐EST bleeding in all 149 patients. Heparin replacement was only a significant risk factor for total‐EST bleeding ( P = 0.033) in DOAC users. Conclusion: Heparin replacement was a significant risk factor for post‐EST bleeding in DOAC users; however, there was no significant difference between the bleeding rate of heparin replacement and that of continuation groups in patients taking warfarin. During EST and precut were significant risk factors for post‐EST bleeding in all patients treated with anticoagulants.